An overview of catalyst development for enhanced green hydrogen production / Wei Shi Ng ... [et al.] - Wei, Shi Ng; Azhar, Nurulfasihah; Mohd Shah, Nur Rabiatul Adawiyah; Rosman, Nurul Nabila; Saidin, Nur Ubaidah; Muslimin, Masliana; Mohamad Yunus, Rozan (Universiti Teknologi MARA, 2024)
The persistent release of greenhouse gases, primarily due to the heavy reliance on fossil fuels in transportation and energy-intensive industries, necessitates urgent research into sustainable alternatives. These sectors, regarded as the foundation of civilisation, make significant contributions to environmental degradation. In response, hydrogen (H2) emerges as a promising energy source capable of meeting global energy needs while reducing harmful emissions. This article provides a comprehensive overview of cutting-edge H2 production technologies, focusing on a critical issue within this landscape: the use of precious metals in catalysts. While precious metals such as platinum have excellent catalytic activity, their scarcity and high cost make widespread implementation difficult. A careful review of catalyst support materials to improve overall performance and stability is also provided. It explores the wider field of catalysts for producing green H2, including needs, recent findings, theoretical effectiveness, and developing approaches to lessen reliance on precious metals. The article concludes with perspectives on the future, promoting a better understanding of the complex interplay between catalyst design, sustainability, and green H2 production